Hepatitis-associated aplastic anaemia: surveillance of frequency, clinico-haematological features, and demographic distribution at a tertiary care hospital in Pakistan - Nawaz, Muhammad Talha; Hameed, Ayesha Nasir; Angez, Meher; Ansari , Ali Hussain; Adil, Salman Naseem (Journal of the Pakistan Medical Association, 2022)
Objective: We aim to document the frequency of HAAA cases among AA patients presenting at a tertiary care hospital, and to determine the most common agents (viral/drug induced) and Clinico-haematological features among HAAA patients at a tertiary care hospital. Methods: This study was a retrospective review, conducted at a tertiary care hospital in Karachi, Pakistan. Results: A total of 21 patients were included in the study. Hepatitis among the HAAA patients was viral in 17 cases, while 4 were idiopathic. All the patients acquired aplastic anaemia within 3-12 months of the Hepatitis episode and most presented with bleeding, bruises and petechiae. Conclusion: This study indicates and proves that presence and prevalence of this disease in the Pakistani population is quite significant. Unlike the rest of the world, HAAA in Pakistan is not entirely of unknown aetiology, most of the cases can be associated with one of the Hepatitis viruses. Keywords: Hepatitis, Aplastic Anaemia, Hepatitis Associated Aplastic Anaemia, IST, HSCT.